The legal perspective on installation of cctv in public places in Malaysia / Rozliana Amir, Mazlinda Mohd Mazlan and Nik Nadiah Nik Mat - Amir, Rozliana; Mohd Mazlan, Mazlinda; Nik Nadiah, Nik Mat (2008)
In Malaysia, Close Circuit Television (CCTV) is widely installed for crime detection and to safeguard the security of the public. The usage of CCTV nowadays is extent to government institutions, offices, public places for instances Public Park, shopping complexes and parking lots. The main objective of the installation is to detect crime as well as to reduce crime rates. However the issue is that how is the data from CCTV is being managed? Besides, how far the information can be disclosed to third party and at what circumstances it infringes the privacy of an individual. By conducting this research, we would like to analyze whether Malaysia have specific law, regulations, guidelines or code of practice imposed on Data user on the usage of CCTV. Thus, we refer to Data Protection Act 1998 in UK, Article 8 of European Convention of Human Right and Malaysian proposed Bill for the purpose of our research. This research also includes several recommendations for government to provide some guidelines for data user for instance data user not only have to put a signage to notify the people that they are being monitored by CCTV but inform the public that the information will be processed and used for the purpose it being installed. For non governmental organizations they have the responsible to increase public awareness on the consequences of the usage of CCTV. Since their image has been recorded, captured and keep for certain period then they should have right to access and to know how the information is being processed.